Photocatalytic TiO2 nanosheets-SiO2 coatings on concrete and limestone: An enhancement of de-polluting and self-cleaning properties by nanoparticle design. (4th July 2022) - Luna, M.; Delgado, J.J.; Romero, I.; Montini, T.; Almoraima Gil, M.L.; Martínez-López, J.; Fornasiero, P.; Mosquera, M.J.
Graphical abstract: Highlights: TNS-SiO2 coatings can be easily created on the limestone and concrete surface. TNS-coatings are active for the removal of common pollutants such as soot and NOx. Adsorbed residual fluoride hinder the coating synthesis and its photo-activity. TNS-coatings show better self-cleaning and antipollution properties than P25-coatings. TNS is a promising active phase for creating transparent photoactive coatings for buildings. Abstract: In this study, we develop TiO2 -SiO2 nanocomposites that can be employed as photoactive coatings to create surfaces with antipollution and self-cleaning properties in urban buildings. In particular, anatase titanium dioxide with a high percentage of {0 0 1} facets, commonly called titania nanosheet (TNS), was used as active phase. This approach allows us to improve the antipollution properties of similar sols based on P25. The obtained TNS were intensively characterized by UV–Vis diffuse reflectance absorption, X-Ray diffraction and transmission electron microscopy to rationalize the sol synthesis and fully understand the photocatalytic performances. Our results clearly show that after treating the titania nanosheets with NaOH to remove adsorbed residual fluoride from the synthesis, they can be easily dispersed and the photocatalytic activity is dramatically improved. This material has been shown to effectively reduce concentrations of NOx, soot and organic dyes under simulated sun light radiation.